ISLAMIC ECONOMICS AND SUSTAINABLE DEVELOPMENT: TOWARDS AN INCLUSIVE AND ETHICAL GLOBAL ECONOMY - Abdur Rohman; Amir Raza; Khalil Zaman (Journal of Noesantara Islamic Studies, 2026)
The growing challenges of economic inequality, environmental degradation, and social exclusion have prompted a search for alternative economic systems. Islamic economics, grounded in principles of justice, equity, and responsible resource management, offers a promising solution to these global issues. This study aims to explore how Islamic economics can contribute to sustainable development by fostering an inclusive and ethical global economy. The research employs a qualitative approach, utilizing interviews with key informants and case studies from countries that have implemented Islamic economic principles. Data collected highlights the alignment of Islamic economics with the goals of sustainable development, emphasizing social welfare, environmental stewardship, and equitable wealth distribution. The study reveals that Islamic economic principles not only promote economic growth but also ensure that such growth benefits all segments of society without compromising environmental integrity. Barriers to the widespread adoption of Islamic economics, such as institutional resistance and limited awareness, are also identified. The findings suggest that integrating Islamic economic principles into global economic systems could significantly contribute to achieving the United Nations' Sustainable Development Goals. This research provides valuable insights for policymakers, business leaders, and scholars seeking to incorporate Islamic economics into development strategies.